El legado del capitán Gómez Márquez a la ciudad de Oaxaca - Manuel Jesús Carrasco Terriza (Huelva en su Historia, 1970)
El capitán Juan Gómez Márquez (Cumbres Mayores, Huelva, 9-4-1664; Antequera de Oaxaca, 6-2-1722) labró su fortuna en Oaxaca con el comercio de la grana y de los tejidos. El inventario de bienes sumaba aproximadamente 440.000 escudos de plata. El 80% fue destinado a fines caritativos, religiosos y de servicios públicos de Oaxaca. Fueron beneficiados todos los edificios religiosos, hospitalarios, educativos y públicos. Entre ellos destacan el acueducto, que se extiende desde el cerro de San Felipe hasta la ciudad, y la reedificación de la Catedral. Oaxaca debe parte del esplendor arquitectónico del siglo XVIII al mecenazgo del capitán Gómez Márquez._______________________________The captain Gómez Márquez (Cumbres Mayores, Huelva, 9th April 1664; Antequera, Oaxaca, 6th February 1722) made up his fortune in Oaxaca by cochineal and textile trade. The amount of his income was nearly 440.000 silver escudos. About the 80% of these founds was spent on charity, religious and public services in Oaxaca, i.e. religious buildings, hospital centres, and public educational edifices. Among those, there are two very important ones to be pointed out: firstly, the aquadut which goes from San Felipe's hill to the city; secondly, the rebuilding of the Cathedral of Oaxaca, which has its highest architectural splendour in 18th century, in part because of the patronage of the captain Gómez Márquez.